Essential Menéndez Pidal and jewels of the study of the language of the XVIth century - Abad Nebot, Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article includes an essential list of the philological work (language, literature and history) of Ramón Menéndez Pidal, and it analyses his studies on the Spanish language in the XVIth century. This article adds other references to the inventory of general studies on the language of the XVIth centuy.